(untitled) (Journal of Humanitarian and Applied Sciences, 2018)
In this study, the water quality of the wells was assessed for six areas in the Qasr al- Ikhayyar area which are (Al-Shorfa, Al-Halifa, Oulad Hussein, Alammariyin, Al-Snad and Al-Karamda) and the Qasr Al-Ikhayyar area of the coastal areas located in north-west of Libya on a line of 13.95o degrees east and 32.7o degree north. The problem of the study is that there is a lack of irrigated crops of economic importance to the country in the study area. This is due to the salinity of the wells used for irrigation. The disappearance of some fruit trees in this area such as lemons, almonds and pomegranates is also caused by the salinity of the resulting wells of sea water intrusion. The study aims to determine the salinity concentration in surface and groundwater wells and their impact on the agricultural environment and public health. The laboratory results showed that all the areas allocated for study are completely free from microbial pollution resulting from wastewater except for the area of the terrace and have been contaminated, and this is due to the presence of some reasons, including the use of natural animal fertilizers on farms in abundance and the presence of some wells The black water sources near the study area are probably more. In terms of physical and chemical, the percentage of total salts for the samples of Regions (4,5 and 6) (Alammariyin, Al- snad and Al-Karamda) respectly was found to be valid and conforming to the specifications, with a value of between 687 - 1185 mg / L. The samples of areas 1.2 and 3 (Al-Shorfa, Al-Halifa and Oulad Hussein) respectly, are not identical to the specifications. As for the major elements such as sodium, potassium and sulfur when compared to their value in the specification, the samples of areas (4-5) (Alsnad and Al karamda) were found to comply with the specification. Samples of Regions No. 1,2,3 and 6 (Al-Shorfa, Al-Halifa, oulad Hussein and Al-Karamda) respectly, the evidence is not in accordance with the specifications applied in the study.